1993
DOI: 10.1007/bf00191945
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of Borna disease virus-specific RNA in secretions of naturally infected horses by the polymerase chain reaction

Abstract: The presence of Borna disease virus (BDV)-specific RNA was traced by the reverse transcriptase-polymerase chain reaction in conjunctival fluid, nasal secretions and saliva of horses which were seropositive but did not have any history of clinical Borna disease. Positive reactions encompassed sequences encoding the p24 BDV-specific protein. Virus specificity of the amplified product was confirmed by hybridization with the respective oligomer probe. Viral infectivity or virus-specific antigen was not found in an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
1

Year Published

1995
1995
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 18 publications
1
31
1
Order By: Relevance
“…12) was positive for both BDV p24 and p40 RNA. The detection of viral RNA in swab samples has also been reported from seropositive, asymptomatic horses (38). Herzog et al (24) reported the isolation of infectious virus from swab samples and lacrimal and parotic glands of diseased horses.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…12) was positive for both BDV p24 and p40 RNA. The detection of viral RNA in swab samples has also been reported from seropositive, asymptomatic horses (38). Herzog et al (24) reported the isolation of infectious virus from swab samples and lacrimal and parotic glands of diseased horses.…”
Section: Discussionmentioning
confidence: 89%
“…In horses, antibody prevalence among healthy animals in Germany has been reported to be approximately 10%, which increases to more than 20% in areas to which the disease is endemic (24,37). Infectious virus has been reported to be incidentally isolated from nasal and lacrimal secretions as well as saliva of diseased horses, and the presence of viral RNA was reported in these secretions in asymptomatic, antibody-positive horses (24,38). In some stables repeated outbreaks of BD are seen over several years, and sometimes numerous animals in one stable develop BD within a period of months (10,33).…”
mentioning
confidence: 99%
“…In naturally BDV-infected horses however, the presence of BDV-specific RNA has been demonstrated by a similar technique in brain tissue [9], and in conjunctival fluid, nasal secretions and saliva [10]. In addition, many seropositive samples from horses were negative by RT-PCR [10], indicating either that BDV is shed irregularly and in intervals or that the BDV genome is sufficiently variable in a number of seropositive animals to evade detection by this technique.…”
Section: Introductionmentioning
confidence: 99%
“…BDV is probably shed in nasal, salivary and 132 G. Dauphin et al conjunctival secretions since BDV-RNA has been detected in these secretions [31,50]. An olfactory route of transmission from horse to horse has been proposed (via the olfactive nerve), either by direct contact with these secretions, or through contaminated food or water.…”
Section: Transmissionmentioning
confidence: 99%